Pengaruh Kelas Kemiringan Lereng dan Penggunaan Lahan terhadap Sifat Fisik Tanah di Kawasan Penyangga Waduk Cirata Kecamatan Cipeundeuy Kabupaten Bandung Barat - Apong Sandrawati; Ade Setiawan; Gilang Kesumah (Soilrens, 2016)
Waduk Cirata  is  one of  impormant  water reservoir  in West  Java.  This  reservoir  was  used  for supporting  power plants  for Java  and Bali’s  area.  It’s  need  more attention  to  keep  the  function continuity  of  Waduk Cirata.  Greenbelt  area  was  one  of  factor determinant  for  establishment  of Waduk Cirata. Landuse change in greenbelt area is a great threat for greenbelt area sustainability, future more to establishment of Waduk Cirata. This research was aimed to study the effect of landuse and slope combination to physical property of soil. The research was conducted in greenbelt area of Waduk  Cirata,  located  in  Margalaksana  and Nenggeleng Village,  Cipeundeuy  District,  Bandung Barat.  The  independent  variable was  three landuse  type  and two  class  of  slope,  so  that  were six combination variable that repeated four times, so there was 24 land unit. This land unit determinedwith  overlay  tools  in ArcGIs software.  Statistical  analysis  used  for determined  the effect  andrelationship between parameter. Based on analysis data, combination of landuse type and class of slope not  influence  bulk density,  porosity,  and permeability  value.  Rubber plantation with  class  of slope 8-15%  has  higher bulk density  (1.24  g/cm3) and higher porosity  (66.7  %),  meanwhile,  the higher of permeability (9.31cm/hour) found in cocoa plantation with class of slope 16-25%.Keywords: greenbelt area, landuse, class of slope, bulk density, porosity, permeability.